Lenograstim 5 µg/kg is not superior to biosimilar filgrastim 10 µg/kg in lymphoma patients undergoing peripheral blood stem cell mobilization after chemotherapy: preliminary results from a prospective randomized study. Issue 5 (15th February 2018) - Marchesi, Francesco; Vacca, Michele; Giannarelli, Diana; Ipsevich, Francesco; Pandolfi, Annino; Gumenyuk, Svitlana; Renzi, Daniela; Palombi, Francesca; Pisani, Francesco; Romano, Atelda; Spadea, Antonio; Papa, Elena; et al.
Abstract : BACKGROUND: Randomized trials comparing chemomobilization efficiency between lenograstim and biosimilar filgrastim are lacking. Our previous retrospective study suggested that lenograstim could be more effective than biosimilar filgrastim when used at the same conventional dosage (5 µg/kg) only in lymphoma patients undergoing peripheral blood stem cell mobilization. We planned a prospective randomized study comparing lenograstim 5 µg/kg with biosimilar filgrastim 10 µg/kg to verify the hypothesis of lenograstim superiority even at half the dosage (stress test). Herein we report data after enrolling 60% of planned patients. STUDY DESIGN AND METHODS: From October 2014 to November 2017, a total of 42 of 70 planned patients with lymphoma were randomly assigned to receive lenograstim 5 µg/kg (21) or biosimilar filgrastim 10 µg/kg (21). Patients were stratified according to treatment line at the time of mobilization (1 or ≥2). Primary endpoint was the rate of achievement of the CD34+ cell collection target dose (≥ 4 × 10 6 /kg). An improvement by 23% was expected to validate the hypothesis of lenograstim superiority. RESULTS: The two cohorts were balanced for all the baseline features. We observed an identical rate of patients able to reach the targeted CD34+ cell dose and of mobilization failures (90.4 and 4.8% in both cohorts) and a perfect equivalence in any of the secondary collection outcomes. The hypothesis of lenograstim superiority was not corroborated at interim analysis. CONCLUSION: Lenograstim at conventional dosage has failed to demonstrate its superiority over biosimilar filgrastim at double the dosage at interim analysis in their first head‐to‐head trial.